Paritas Dengan Usia Menopause Pada Wanita Usia 45-59 Tahun - Adhika Wijayanti; Sartika Dwi Yolanda Putri (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Menopause is a period of cessation of the menstrual cycle forever for women who previously experienced menstruation every month, which is caused by the number of follicles that experience atresia continues to increase, until there are no more follicles available, and in the last 12 months experience amenorrhea (Fitri, 2017). The factors that influence the occurrence of menopause among women were the age at first menstruation (menarche), number of children, age at delivery, use of contraception, smoking and socioeconomic status (Kumlasari, 2012). The purpose of this study was to determine the relationship between the parity and the age of menopause in women aged 45-59 years at the Palembang Social Health Center. A cross sectional approach was the method used in this study and it was analytic. The population of this study was all women aged 45-59 years at the Palembang Social Health Center. The sample was 100 people chosen by using an accidental sampling technique. The data were collected by using the direct measurements, interviews, filling out questionnaires and the data were analyzed by using the Chi-Square statistical test. The results of the study showed that there was a significant relationship between parity and the age of menopause in women aged 45-59 years at the Palembang Social Health Center in 2019, with a p value of parity = 0.000 < α (0.05).